Plasmin inactivation in Plasma - Haselager, E. M; Goote, Th. M; Vreeken, J (Thrombosis and Haemostasis, 1976)
Inhibition and inactivation of plasmin is ascribed to α2-macroglobulin, α1-antitrypsin and c1-esterase inhibitor. In an “overall” inactivation test of plasmin in plasma, which comes perhaps closest to rapid inactivation of plasmin in the circulating blood, we only found a correlation between the immunological concentration of α2-macroglobulin and the plasmin-inac-tivating capacity of the plasma, but no correlation with the immunological concentration of the other inhibitors mentioned. Therefore, α2-macroglobulin seems to be the most important plasmin inhibitor in relation to thrombosis.